Shared and distinct patterns of dynamical degree centrality in bipolar disorder across different mood states - Sun, Fuping; Liu, Zhening; Yang, Jun; Fan, Zebin; Xi, Chang; Cheng, Peng; He, Zhong; Yang, Jie (Frontiers in Psychiatry, 2022)
Background Previous studies have probed the brain static activity pattern in bipolar disorder across different states. However, human intrinsic brain activity is time-varying and dynamic. There is a lack of knowledge about the brain dynamical pattern in bipolar disorder across different mood states. Methods This study used the dynamical degree centrality (dDC) to investigate the resting-state whole-brain dynamical pattern at voxel-wise in a total of 62 bipolar disorder (28 bipolar depression [BD], 13 bipolar mania [BM], 21 bipolar euthymia [BE]) and 30 healthy controls (HCs). One-way analysis of covariance (One-way ANOVA) was applied to explore the omnibus differences of the dDC pattern across all groups, and Pearson correlation analysis was used to evaluate the relationship between the dDC variability in detected regions with clinical symptom severity. Results One-way ANOVA analysis showed the omnibus differences in the left inferior parietal lobule/middle occipital gyrus (IPL/MOG) and right precuneus/posterior cingulate cortex (PCUN/PCC) across all groups. Post-hoc analysis revealed that BD showed decreased dDC in the IPL/MOG compared with all other groups, and both BD and BM exhibited decreased dDC in the PCUN/PCC compared with BE and HCs. Furthermore, correlation analysis showed the dDC variability of the IPL/MOG and PCUN/PCC negatively correlated with the depression symptom levels in all patients with bipolar disorder. Conclusions This study demonstrated the distinct and shared brain dynamical pattern of the depressive, manic, and euthymia states. Our findings provide new insights into the pathophysiology of bipolar disorder across different mood states from the dynamical brain network pattern perspective.